HIV-Infected African Americans are Willing to Participate in HIV Treatment Trials - Garber, Mandy (Springer-Verlag, 2007)
BACKGROUND: Despite the high prevalence rates of HIV infection in the African-American community, African Americans remain underrepresented in HIV treatment trials. OBJECTIVE: (1) To develop a questionnaire that measures attitudes and concerns about HIV treatment trials among HIV-infected African Americans at a university-based clinic. (2) To determine actual participation rates and willingness to participate in future HIV treatment trials among HIV-infected African Americans at a university-based clinic. DESIGN: Questionnaire development and cross-sectional survey. SETTING, PARTICIPANTS, AND MEASUREMENTS: In a sample of 200 HIV-infected African-American adults receiving medical care at the Pittsburgh AIDS Center for Treatment (a university-based ambulatory clinic), we assessed research participation rates and willingness to participate in future HIV treatment trials, trust in the medical profession, sociodemographic characteristics, attitudes, and concerns about HIV treatment trials. MAIN OUTCOME MEASURES: Research participation rates and willingness to participate in future HIV treatment trials. RESULTS: Only 57% of survey respondents had ever been asked to participate in an HIV treatment trial but 86% of those asked said yes. Prior research participation was significantly related to willingness to participate in future HIV treatment trials (P = .001). Contrary to previous studies, neither trust/distrust in the medical profession nor beliefs about the dishonesty of researchers was associated with research participation rates or willingness to participate in future HIV treatment trials. CONCLUSIONS: Having never been asked to participate in research is a major barrier to the participation of HIV-infected African Americans in HIV treatment trials. African Americans who seek medical care for HIV infection should be asked to participate in HIV treatment trials.